KREDIBILITAS KOMUNIKATOR DALAM MENUMBUHKAN SIKAP KELOMPOK TANI HUTAN DI KABUPATEN SUMEDANG - Iriana Bakti; Trie Damayanti; Aang Koswara (Universitas Bunda Mulia, 2016)
The communicators in environment communication has a very important role in establishing effectivecommunication in the environment with their audience. A communicator tried to resuscitatecommunity to always care to the surrounding environment . The presence of a credible environmentalcommunicator can reduce the gaps in knowledge about environmental issues, and may even build apositive attitude towards the development of forestry. Studies on the credibility of communicator inenvironment communication is intended to determine the skills and increasing confidence ofcommunicators KTH members attitude towards forestry development. The research method isdescriptive survey using a questionnaire as a primary research instrument. The results showed that (1)the environmental communicators are people who have considerable expertise in explaining themessage, and answer questions about the message, so as to foster a positive attitude towards thedevelopment of forestry KTH members. (2) Communicators environment is a trustworthy person,being able to practice the material presented and able to encourage members of KTH to be able topractice it conveys, so as to foster a positive attitude towards the development of forestry KTHmembers. (3) Based on its expertise in explaining the message, and answer questions about about themessage, as well as its belief in practice the messages conveyed in, and encourage members of KTH tobe able to practice it conveys, the communicator environment has a high degree of credibility, so as tofoster a positive attitude member KTH on development of forestry. To optimize the implementation offorestry development, forestry should recruit young people so to become members of KTH, andforestry has to more concerned about environmental issues.Keywords: communicator, credibility, expertise, trustworthiness, attitude